Excitatory effects of calcitonin gene‐related peptide (Cgrp) on superficial sp5c neurons in mouse medullary slices - Zheng, Fang; Nixdorf-Bergweiler, Barbara; van Brederode, Johannes; Alzheimer, Christian; Meßlinger, Karl (International Journal of Molecular Sciences, 2021)
The neuromodulator calcitonin gene‐related peptide (CGRP) is known to facilitate noci-ceptive transmission in the superficial laminae of the spinal trigeminal nucleus caudalis (Sp5C). The central effects of CGRP in the Sp5C are very likely to contribute to the activation of central nocicep-tive pathways leading to attacks of severe headaches like migraine. To examine the potential im-pacts of CGRP on laminae I/II neurons at cellular and synaptic levels, we performed whole‐cell patch‐clamp recordings in juvenile mouse brainstem slices. First, we tested the effect of CGRP on cell excitability, focusing on neurons with tonically firing action potentials upon depolarizing current injection. CGRP (100 nM) enhanced tonic discharges together with membrane depolarization, an excitatory effect that was significantly reduced when the fast synaptic transmissions were phar-macologically blocked. However, CGRP at 500 nM was capable of exciting the functionally isolated cells, in a nifedipine‐sensitive manner, indicating its direct effect on membrane intrinsic properties. In voltage‐clamped cells, 100 nM CGRP effectively increased the frequency of excitatory synaptic inputs, suggesting its preferential presynaptic effect. Both CGRP‐induced changes in cell excitability and synaptic drives were prevented by the CGRP receptor inhibitor BIBN 4096BS. Our data provide evidence that CGRP increases neuronal activity in Sp5C superficial laminae by dose‐dependently promoting excitatory synaptic drive and directly enhancing cell intrinsic properties. We propose that the combination of such pre‐ and postsynaptic actions of CGRP might underlie its facilitation in nociceptive transmission in situations like migraine with elevated CGRP levels.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Calcitonin gene‐related peptide; Cell excitability; Excitatory postsynaptic currents; Migraine; Spinal trigeminal nucleus caudalis